2017
DOI: 10.5539/ijms.v9n1p139
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Store Internal Dimensions on the Customer Loyalty: A Comparative Study between Sameh Mall and Khalid Mall

Abstract: Customer loyalty is among the factors that increase the competitive advantage of stores and raise its market share among the other stores. Nowadays, the issue of loyalty and customer loyalty is becoming a trend among all stores even the small stores and supermarkets that are found in the local provinces (Rajic & Dado, 2013). The current study aims at understanding the influence of the internal dimensions of the store on the customer loyalty between Sameh mall and Khalid mall. The variables which were taken int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The results of these research works reported that store atmosphere would have a positive impact on store patronage behavior (e.g. Joudeh, 2017;Yoo and MacInnis, 1998). Another identified antecedent was the store image and its effect on store patronage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of these research works reported that store atmosphere would have a positive impact on store patronage behavior (e.g. Joudeh, 2017;Yoo and MacInnis, 1998). Another identified antecedent was the store image and its effect on store patronage.…”
Section: Literature Reviewmentioning
confidence: 99%